Pengaruh Direct Marketing dan Personal Selling PT. Malindo Feedmill Makassar terhadap Kepuasan Pelanggan - Ardiantho Halili; Andi Vita Sukmarini; Fitriana Fitriana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to determine the influence of direct marketing and personal selling by PT Malindo Feedmill Makassar on customer satisfaction, and to analyze which variable has a more dominant significant effect on customer satisfaction at PT Malindo Feedmill Makassar. The research was conducted in Pinrang Regency, Sidrap Regency, and Soppeng Regency with a sample size of 50 layer farmers using feed from PT Malindo Feedmill. The data analysis was descriptive to explain the research data. For analyzing quantitative data, multiple linear regression analysis was used with SPSS version 29. The results show that the direct marketing and personal selling variables simultaneously affect customer satisfaction at PT Malindo Feedmill Makassar, with the coefficient of determination (adjusted R square) indicating that the independent variables in this study explain 32% of the variance, while the remaining 68% is influenced by variables outside the scope of this study. Partially, both direct marketing and personal selling variables have a significant and positive impact on customer satisfaction at PT Malindo Feedmill Makassar.